2000
DOI: 10.1002/1097-0231(20001215)14:23<2147::aid-rcm145>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the intensities of lysine-terminated tryptic peptide ions in matrix-assisted laser desorption/ionization mass spectrometry

Abstract: Tryptic digests of three proteins are reacted with O‐methylisourea in order to convert lysine residues to homoarginines. The resulting homoarginine‐terminated peptides exhibit more intense MALDI mass spectral peaks than their lysine‐terminated predecessors. This simple chemical reaction should therefore facilitate protein sequencing and mass mapping. Copyright © 2000 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(124 citation statements)
references
References 15 publications
7
117
0
Order By: Relevance
“…Therefore, in early study, the method by converting lysine into homoarginine (guanidination derivatization) was established to increase the gas-phase basicity of lysine-containing peptides [14,15] . Hale et al [16] applied O-methylisourea to converting the İ-amino group of lysine into homoarginine and obtained a higher detection sensitivity in detecting peptides by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS).…”
Section: Derivatization Of Amino Groupsupporting
confidence: 80%
“…Therefore, in early study, the method by converting lysine into homoarginine (guanidination derivatization) was established to increase the gas-phase basicity of lysine-containing peptides [14,15] . Hale et al [16] applied O-methylisourea to converting the İ-amino group of lysine into homoarginine and obtained a higher detection sensitivity in detecting peptides by matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS).…”
Section: Derivatization Of Amino Groupsupporting
confidence: 80%
“…The other side-chain cleavage fragments are also observed from the free radical-induced decomposition of the lithium adduct of the lysine modified peptide 2a. It is of note that the fragment 2h ([a 5 ϩ Li] ϩ , m/z 463) may be derived from a radical that migrates along the peptide backbone from the radical on the ␣-carbon of the lysine side chain [16]. Fragments 2e, 2i, and 2j have also been observed in the decomposition of Li adduct of 1a (Scheme 2).…”
Section: Cid Experiments Of Modified Peptides At Lysine Sites Using Ementioning
confidence: 99%
“…The sequencing is often accomplished using tandem mass spectrometry (MS/MS) by collision-induced dissociation (CID) or electron capture dissociation (ECD) of protonated species [3,4]. Chemical modification of peptides or proteins has also provided strategies that are helpful in assignment of peptide sequence, enhancement of the MS sensitivity [5], and, importantly, in protein quantification [6]. Even though database searches for protein identification are primarily based on b-and y-ions observed in MS/MS spectra, complex fragmentation patterns can result from the ECD process and improve the sequence coverage in protein identification [7,8].…”
mentioning
confidence: 99%
“…The guanidination, leading to C-terminal lysines being converted into homoarginines (ϩ42 Da), can be selectively and quantitatively performed with O-methylisourea at high pH and does not affect the peptide amino terminus or other side groups. The resulting homoarginine has an even higher pKa than arginine, and it has previously been shown that a rise of the basicity of lysines increases their relative abundances in MALDI mass spectra by enabling enhanced charge retention [27,28]. Furthermore, it allows unambiguous differentiation of Lys (128.18 Da) and Gln (128.13 Da) by mass spectrometry.…”
Section: De Novo Sequence Analysismentioning
confidence: 99%